Reward System and Its Impact on Employee Motivation in Nepalese Commercial Banks - Khadka, Bibek (Nepalese Journal of Management, 2025)
This study examines the reward system and its impact on employee motivation in Nepalese commercial banks. Employee motivation is the dependent variable. The selected independent variables are salary increment, bonus and commission, promotion, job growth, and retirement benefit. The primary source of data is used to assess the opinions of respondents regarding salary increment, bonus and commission, promotion, job growth, retirement benefit, and employee motivation. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of reward system and its impact on employee motivation in Nepalese commercial banks. The study showed a positive impact of salary increment on employee motivation. It indicates that increase in salary leads to increase in motivation level of employees. Similarly, the study showed a positive impact of bonus and commission on employee motivation. It indicates that higher the bonus and commission, higher would be the employee motivation. Likewise, the study showed a positive impact of job growth on employee motivation. It indicates that opportunities of job growth leads to increase in employee motivation. Further, the study also showed a positive impact of promotion on employee motivation. It indicates that effective promotion policy leads to increase in employee motivation. In addition, the study showed a positive impact of retirement benefit on employee motivation. It indicates that retirement benefit leads to increase in employee motivation.